The Knowledge-Innovation Pathway: How Organizational Culture, Structure, and Technology Drive Process Improvement and Product Innovation - Abbas, Muzaffar; Mahmood, Haider; Furqan, Maham; Qaralleh, Thikryat Jibril (Journal of Education Culture and Society, 2025)
Aim. This study investigates the interplay between process improvement (PRI), organizational innovation (OIN), knowledge sharing (KWS), and product innovation (PIN) in small commercial enterprises, framed within the Resource-Based View (RBV) paradigm. Method. Given the relationship of the variables, the Structural equation modeling (SEM) was the most appropriate technique employed to analyze the relationships among these constructs, focusing on mediation effects and pathways influencing innovation outcomes. The results show a direct and positively significant relationship between PRI, OIN, KWS, and PIN, underscoring their synergistic roles in driving innovation. Whereas Knowledge sharing (KWS) mediates the influence of organizational factors (cultural norms, organizational structure and use of advanced technological infrastructure) on product innovation (PIN). The process improvement (PRI) acts as an intermediary between knowledge transfer, organizational change, and PIN. Organizational Innovation (OIN) directly enhances both product innovation (PIN) and knowledge-sharing practices, fostering a culture of continuous improvement. Results. The findings validate RBV’s relevance in small enterprises, highlighting how intangible resources (e.g., knowledge, processes) drive competitive advantage through innovation. The dual mediation roles of KWS and PRI clarify mechanisms linking organizational capabilities to innovation outcomes. Conclusion. Small enterprises should prioritize the cultivation of a knowledge-sharing culture and robust technological infrastructure to amplify innovation, aligning process improvement initiatives with organizational change strategies to bridge gaps between knowledge and product development.